Knowledge, Attitude and Practice of Blood Glucose Monitoring in Rural Area among Diabetic Patients - Shabnum, Saima; Sarwar, Hajra (International Journal of Social Sciences and Management, 2018)
Background: Diabetes is main and growing health issue affecting more than 171 million peoples worldwide and the number is expected to rise to 366 million by 2030. Type 2 Diabetes will keep on accounting for 90% of all the cases. According to the WHO, Pakistan positioned seventh in pervasiveness of Diabetes. In 2011, the assessed pervasiveness of diabetes in Pakistan was generally in excess of 350 million and it is depended upon to be in excess of 550 million by year 2030. In Pakistan 9.5% of urban and 9.4% of the provincial population experience the bad effects of type 2 diabetes. Objective: The reason for this investigation was to survey learning, conduct in regards to blood glucose observing among diabetic in rural group, Lahore. Descriptive cross sectional investigation configuration was led to evaluate learning, disposition and routine with regards to blood glucose monitoring and a sample size of 100 participants was selected for this study through convenient sampling. Data was collected from the adult males and females of Husain Abad community. Result: The result show that there was low level of knowledge, somewhat positive attitudes but very low level of practices regarding the diabetic control and glucose monitoring among the participants. Conclusion: In conclusion, it is stated that this research study the knowledge of participants towards the diabetes was not good except the definition of diabetes. The attitude was comparatively positive and good for following different blood sugar controlling measures. The practices were very poor. No one was following regular exercises, dietary modifications etcetera. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 225-230